The Quality of Banking Financial Reporting Information Before and After IFRS 9 Implementation - J Jasman; A Aminatunnaza (Jurnal ASET (Akuntansi Riset), 2023)
This research aims to test differences in the quality of banking financial reporting information before and after the implementation of IFRS 9 which was adopted as PSAK 71 in Indonesia. Data was acquired from the annual and quarterly financial reports of conventional banking sector listed on the Indonesia Stock Exchange 2018-2021. The data analysis technique used the Wilcoxon signed ranks test to investigate the differences in accrual quality, and the paired sample t test to investigate the differences in value relevance. The results found that there are significant differences in the financial reporting information quality before and after PSAK 71 implementation in terms of accrual quality. After PSAK 71 implementation, managers used more discretion to influence accounting figures than before the PSAK 71 implementation. The main factor that may cause this difference is the global economic crisis that hit in 2020-2021 due to the Covid-19 pandemic and other institutional changes that occurred along with the PSAK 71 implementation. However, there is no significant difference in value relevance before and after PSAK 71 implementation. As a result, although the PSAK 71 implementation theoretically has a positive impact on increasing value relevance, this condition may be covered by the impact of the economic crisis during the Covid-19 pandemic which coincides with the PSAK 71 implementation. The significance of this study is to examine whether there are differences in the quality of bank financial reporting information before and after implementing PSAK 71 from the perspective not only accounting but also the market.